A study of oxygen-enriched reactivity-controlled compression ignition combustion in a diesel research engine under varying loadings and premixed ratios - Altun, Sehmus; Firat, Mujdat; Okcu, Mutlu; Varol, Yasin (Taylor & Francis Inc, 2024)
High-Efficiency Reactivity-Controlled Compression Ignition (RCCI) with ultra-low NOx and Soot emissions still needs to be investigated in terms of its operating conditions such as high load range and increasing CO and unburnt HC emissions, which are critical issues to be addressed before implementation for practical engines. Therefore, as the main factors affecting the RCCI combustion are the engine load and premixed ratio of low reactivity-fuel, in the present study, the effect of these parameters in a modified single-cylinder research engine equipped with common-rail direct injection (CRDI) on RCCI combustion are experimentally studied in detail along with oxygen-enrichment environment at two stages. At first, the effect of engine load (20%, 40%, and 60% of max.torque at 2400 rpm) and premixed ratio (Rp, 15% to 60% in increments of 15%) in enriched O-2 environment to 29% was investigated while in second stage, increasing oxygen amount in intake air under low-mid load range (40% of max.torque) and premixed ratio (Rp, 30% replacement of total energy given to engine) was investigated, and compared with atmospheric air conditions. Following results were noted in the first part of the study when the engine load was increased at all premixed ratios; in-cylinder pressure and rate of heat release increased with shortening the ignition delay, IMEP increased up to 12% along with decrease in CO (by 38%), unburned HC (by 32%) and smoke opacity (by 24%) with the cost of increasing NOx emissions by 162% when compared to atmospheric air. In the second stage, increase in oxygen ratio resulted in decrease of ignition delay period and prolong combustion duration that have led to RCCI engine performance to be better and sharp reductions in the incomplete combustion emissions up to 36%. It was concluded that enriched oxygen is a beneficial way for reducing exhaust emissions during RCCI combustion at wider operating conditions.
Keywords: RCCI; oxygen-enrichment; combustion; emissions; diesel engines